Study of Retail Applications with Virtual and Augmented Reality Technologies - Kumar, T. Senthil (Journal of Innovative Image Processing, 2021)
The rapidly emerging virtual reality (VR) and augmented reality (AR) technologies have greatly improved the digital shopping experience and retail selling environment. In terms of practical applications and academic research, fragmentation in VR and AR contributes to the technology’s multidisciplinary roots in terms of applications. In this paper, the retail applications and research works that make use of VR and AR technology are compared and analyzed. The implementation, consumer acceptance, applications, issues and other related terms are compared. This study establishes a foundation for future work in the retail applications field.